Sudden sensorineural hearing loss is associated with chronic rhinosinusitis: population-based study. Issue 6 (27th April 2016) - Hung, S H; Lin, H C; Kao, L T; Wu, C S; Chung, S D
Abstract: Background: This study aimed to evaluate the association of chronic rhinosinusitis with sudden sensorineural hearing loss using a population-based database. Methods: Sampled subject data were obtained from the Taiwan Longitudinal Health Insurance Database 2000. A total of 3325 patients with sudden sensorineural hearing loss were identified and 9975 controls were randomly selected. A conditional logistic regression was used to calculate the odds ratio for having been previously diagnosed with chronic rhinosinusitis, for cases and controls. Results and conclusion: The adjusted odds ratio of having prior chronic rhinosinusitis among cases compared to controls was 1.36 (95 per cent confidence interval = 1.16–1.60). The significant relationship between sudden sensorineural hearing loss and chronic rhinosinusitis was most pronounced among those patients aged 44 years or less (compared to controls) (odds ratio = 2.18; 95 per cent confidence interval = 1.63–2.92). However, the significant relationship between sudden sensorineural hearing loss and prior chronic rhinosinusitis was not sustained for patients older than 60 years compared to controls.